Kiegészítések az Anjou-kori Oklevéltár XXII., XXIX. és XXX. köteteihez (1338, 1345, 1346) - Piti Ferenc (Acta Universitatis Szegediensis : acta historica, 2022)
The author of this article published his books mentioned in the title 8–10 years ago in which there are more than 2500 excerpts of charters illustrating the Hungarian Angevin era (1301–1387) from the years 1338, 1345 and 1346. This study contains some extracts which were unpublished, due to different causes, in the above-titled books, completing this way those ones.